What’s New in Neurofibromatosis? Proceedings From The 2009 NF Conference: New Frontiers - Kissil, Joseph (2010)
The NF Conference is the largest annual gathering of researchers and clinicians focused on neurofibromatosis and has been convened by the Children’s Tumor Foundation for over 20 years. The 2009 NF Conference was held in Portland, Oregon from June 13(th) – June 16(th), 2009 and co-chaired by Kathryn North from the University of Sydney and The Children’s Hospital at Westmead, Sydney, Australia; and Joseph Kissil from the Wistar Institute, Philadelphia. The Conference included 80 platform presentations in 9 sessions over 4 days; over 100 abstracts presented as posters; and three Keynote presentations. To date, there have been tremendous advances in basic research in the pathogenesis of neurofibromatosis, and more recently in progress toward identifying effective drug therapies and the commencement of neurofibromatosis clinical trials. The NF Conference attendees have significantly increased (doubling from 140 in 2005 to 280 attending in 2009) with a significant increase in attendance of physicians and clinical researchers. Correspondingly the NF Conference scope has expanded to include translational research, clinical trials and clinical management issues while retaining a core of basic research. These themes are reflected in the highlights from the 2009 NF Conference presented here.